Unravelling colonial weaving - Mutu, Margaret (Stroppy old women: 52 Kiwi women, who've been around long enough to know, tell you what's wrong with the world, 2015)
What do ... Judith Ablett-Kerr, Pinky Agnew, Donna Akersten, Judith Baragwanath, Janet Beech, Carole Beu, Rob Broughton, Judy Callingham, Trish Costigan, Valerie Davies, Lindsey Dawson, Eve de Castro-Robinson, Debbie Dorday, Dorothy Dudek Vinicombe, Anne Else, Jacquie Fahey, Peggy Fairbairn-Dunlop, Chris Fletcher, Tui Flower, Emerald Gilmour, Tina Grenville, Ruth Harley, Rosie Horton, Glenda Hughes, Sue Kedgley, Jan Kemp, Anne Kennedy, Shona Laing, Helen Leach, Vinka Lucas, Sue McCauley, Elizabeth McRae, Marama Martin, Margaret Mutu, Frances Pitsilis, Ruth Pretty, Wendy Pye, Jenny Rankine, Cecilie Rushton, Catherine Saunders, Karen Soich, Pieter Stewart, Anne Thorp, Mary-Jane Tomasi, Jools Toppp, Jodi Vaughan, Prue Wallis, Ans Westra, Reina Whaitiri, Dale Williams, Margaret Wilson and Alice Worsley ... have in common? They're all irate about something, sounding off on topics from ageing to architecture, shop assistants to short skirts, tablecloths to technology, and many more, in the female follow-up to the popular Grumpy Old Men books. These strops are even more controversial, hard-hitting and funny than the male versions. This is the perfect gift for stroppy old women of all ages.
Keywords: wāhine māori

The State of Māori rights - Mutu, Margaret (Huia, 2015)
The State of Maori Rights brings together a set of articles written between 1994 and 2009. It places on record the Maori view of events and issues that took place over these years, issues that have been more typically reported to the general public from a 'mainstream' media perspective. It is an important documentation of these fifteen years of New Zealand history, recording the assertion of Maori rights as the indigenous people of Aotearoa New Zealand, focusing on Maori issues and experiences and written from a Maori perspective.
Keywords: civil Rights; colonisation; crown violence; foreshore and seabed act 2004; government relations; intergenerational trauma; kāwanatanga; mana motuhake; māori electorates; māori rights; race relations; racism; te pāti māori; tiriti o waitangi/treaty of waitangi; voting; waitangi tribunal

Chapter 8: 'The sea I never gave': Fisheries Settlements - Mutu, Margaret (Treaty of Waitangi settlements, 2015)
Source: National Library of New Zealand Te Puna Matauranga o Aotearoa, licensed by the Department of Internal Affairs for re-use under the Creative Commons Attribution 3.0 New Zealand Licence.
Keywords: fisheries; tiriti o waitangi/treaty of waitangi; treaty settlements